The role of filamins in mechanically stressed podocytes. Issue 5 (16th April 2021) - Greiten, Jonas K.; Kliewe, Felix; Schnarre, Annabel; Artelt, Nadine; Schröder, Sindy; Rogge, Henrik; Amann, Kerstin; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole
Abstract: Glomerular hypertension induces mechanical load to podocytes, often resulting in podocyte detachment and the development of glomerulosclerosis. Although it is well known that podocytes are mechanosensitive, the mechanosensors and mechanotransducers are still unknown. Since filamin A, an actin‐binding protein, is already described to be a mechanosensor and mechanotransducer, we hypothesized that filamins could be important for the outside‐in signaling as well as the actin cytoskeleton of podocytes under mechanical stress. In this study, we demonstrate that filamin A is the main isoform of the filamin family that is expressed in cultured podocytes. Together with filamin B, filamin A was significantly up‐regulated during mechanical stretch (3 days, 0.5 Hz, and 5% extension). To study the role of filamin A in cultured podocytes under mechanical stress, filamin A was knocked down (Flna KD) by specific siRNA. Additionally, we established a filamin A knockout podocyte cell line (Flna KO) by CRISPR/Cas9. Knockdown and knockout of filamin A influenced the expression of synaptopodin, a podocyte‐specific protein, focal adhesions as well as the morphology of the actin cytoskeleton. Moreover, the cell motility of Flna KO podocytes was significantly increased. Since the knockout of filamin A has had no effect on cell adhesion of podocytes during mechanical stress, we simultaneously knocked down the expression of filamin A and B. Thereby, we observed a significant loss of podocytes during mechanical stress indicating a compensatory mechanism. Analyzing hypertensive mice kidneys as well as biopsies of patients suffering from diabetic nephropathy, we found an up‐regulation of filamin A in podocytes in contrast to the control. In summary, filamin A and B mediate matrix‐actin cytoskeleton interactions which are essential for the adaptation of cultured podocyte to mechanical stress.